2003
DOI: 10.1002/adfm.200390017
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Synthesis of Size‐Controlled Polycrystalline Ruthenium Nanoparticles in the Presence of Alcohols

Abstract: Ruthenium nanoparticles of controlled size have been prepared by decomposition of the organometallic precursor Ru(cod)(cot) (cod = 1,5‐cyclooctadiene, cot = 1,3,5‐cyclooctatriene) under an H2 atmosphere in either a pure alcohol or an alcohol/THF mixture as solvent and in the absence of further stabilizer. The particles were characterized by transmission electron microscopy (TEM), high‐resolution electron microscopy (HREM), X‐ray diffraction (XRD), wide‐angle X‐ray scattering (WAXS), and X‐ray photoelectron spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
0
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(128 citation statements)
references
References 60 publications
9
114
0
5
Order By: Relevance
“…3-6 nm (Fig. 7) [57]. A similar trend, namely size decrease, is observed upon changing MeOH for higher alcohols.…”
Section: Stabilization By the Reaction Mediumsupporting
confidence: 68%
“…3-6 nm (Fig. 7) [57]. A similar trend, namely size decrease, is observed upon changing MeOH for higher alcohols.…”
Section: Stabilization By the Reaction Mediumsupporting
confidence: 68%
“…In our case, the presence of grafted ≡Si-C8 fragments on the su face of the particles was evidenced by IR spectroscopy and solid state 13 C CP-MAS NMR. This is different from the organosilane functionalized gold nanocrystal prepared by Fan et al [17] where the silane function is in the external layer of the micelle.…”
Section: Introductionmentioning
confidence: 61%
“…These small metallic particles were characterized by elemental analysis, TEM, IR and solid state 13 C MAS NMR. It was observed that the smallest particles were obtained for the lowest Si/Ru ratio (0.2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following on from this, Santini and co-workers undertook a systematic study of the synthesis of Ru-NPs from Ru(COD)(COT) under various conditions, particularly in imidazolium ILs based on the bis(trifluoromethylsulfonyl)imide (NTf 2 -) ion, rendering highly interesting results [58]. Firstly, it was uncovered that, unlike in traditional solvents [59], decreasing the temperature of decomposition (hence decreasing rate of nucleation) leads to smaller NPs. Furthermore, it was seen that stirring during the decomposition has a negative impact on the size distribution.…”
Section: Synthesis and Characterisation Of Ru-nps In Ionic Liquidsmentioning
confidence: 99%